POLA PENANGANAN LANJUT USIA (STUDI DI PANTI SOSIAL THERESNA WERDHA PSTW) INAKAKA KECAMATAN TELUK AMBON) - Hobarth Williams Soselisa (JURNAL BADATI, 2024)
The pattern of handling the elderly at the Tresna Werdha Ina-kaka Ambon Social Home is carried out in accordance with handling procedures, handling costs, treatment programs and other indicators which are supporting and inhibiting factors in handling the elderly at the Tresna Werdha Ina-kaka Ambon.The aim of this research is to describe and analyze the treatment patterns for the elderly studied at the Theresna Werdha Inakaka Passo Ambon.This type of research is descriptive qualitative. Data collection methods are observation, in-depth interviews, FGD and documentation studies. Data was collected from informants who came from the Head of the Regional Integrated Implementation Unit (UPTD) of the Theresna Werdha Social (PSTW) Inakaka. Social Workers, Officers, Staff and Employees of the Theresna Werdha Social (PSTW) Inakaka. elderly (elderly) who are in the Regional Integrated Implementation Unit (UPTD) of the Theresna Werdha Social (PSTW) Inakaka.The service procedures that have been established by the UPTD Tresna Werdha Inakaka Passo Ambon have been running well in accordance with standard operational procedures, made as simple as possible so that they can be easily understood by the elderly and elderly families on the one hand and on the other hand there are There are four stages used to recruit elderly people, namely the initial approach stage, acceptance stage, guidance stage and termination stage.The service costs that have been budgeted by the government through the UPTD of the Tresna Werdha Inakaka Passo Ambon can be managed well and provide services to the elderly and there are no fees charged to the elderly through registration, getting various services until the elderly are terminated.A supporting factor in providing services to the elderly is the cooperation carried out by the Tresna Werdha Inakaka Passo Ambon Institution UPTD with various regional agencies/social organizations, making it easier for the institution to provide effective and efficient services to the elderly.The obstacles faced by the Tresna Werdha Inakaka Passo Ambon UPTD in providing services to the elderly are the limited quality and quantity of human resources (HR) and social workers who are professionals in their field, as well as only one person cooking and limited facilities and infrastructure available.